Measuring "group cohesion" to reveal the power of social relationships in team production - Simon Gächter; Chris Starmer; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
We introduce "group cohesion" to study the economic relevance of social relationships in team production. We operationalize measurement of group cohesion, adapting the "oneness scale" from psychology. A series of experiments, including a pre-registered replication, reveals strong positive associations between group cohesion and performance assessed in weak-link coordination games, with high-cohesion groups being very likely to achieve superior equilibria. In exploratory analysis, we identify beliefs rather than social preferences as the primary mechanism through which factors proxied by group cohesion influence group performance. Our evidence provides proof-of-concept for group cohesion as a useful tool for economic research and practice.
Keywords: C92; D91; 330; Social relations; work group; group decision; game theory; experiment; Soziale Beziehungen; Arbeitsgruppe; Gruppenentscheidung; Spieltheorie; Experiment